Evaluation of a sustainable self compacting concrete using destructive and non-destructive testing. (2022) - Tripathi, Deep; Kumar, Rakesh; Mehta, P.K.; Singh, Amrendra
Abstract: The main components of concrete are cement and river sand (R-sand). Due to excessive production of cement, CO2 emission also increases which causes air pollution. On using R-Sand, large scale depletion of natural sources creates environmental problems. In view of the increasing national and global consensus on the environmental protection, the governments have put restrictions on mining of R-Sand from the river beds. To overcome these problems, there is a need of cost effective alternatives materials so as to make the construction sustainable without compromising its quality. In the production of Self Compacting Concrete (SCC), fly ash (FA) is utilized as an additional cementitious ingredient, which improves its performance. It solves the problem of FA disposal and environmental pollution too. The manufactured sand (M-sand) is also an alternative material which may solve the problem of shortage of R-Sand, if found suitable. In this study, M-Sand and FA were incorporated in the preparation of a sustainable SCC. After optimisation of FA and M-sand doses in the final mix, two types of SCC mixtures were developed: M-1, which consisted of 100% OPC + 100% R-Sand, and M-2, which consisted of 80% OPC + 20% FA + 50% R-Sand + 50% M-sand. Fresh properties of all SCCs were determined as per EFNARC/BIS recommendations. For destructive testing standard size specimens were cast to determine desired strengths after curing in tap water for 90 days. Rebound Hammer (RH) and Ultrasonic Pulse Velocity (UPV) were utilised in Non-Destructive Testing (NDT) to determine the strength, homogeneity, and integrity of both SCCs. Further, the water absorption of the specimen was measured up to 90 days. XRD analysis was also performed.